Hospital-Based Integrative Medicine A Case Study of the Barriers and Factors Facilitating the Creation of a Center - Coulter, Ian D. (RAND Corporation, 2008)
This study tracks the establishment of a single hospital-based integrative medicine center. Although some factors clearly worked in favor of the center, the hospital had few models to guide it and no experience in creating such a clinic. Thus, it made many decisions in the areas of administration, finance, and legal issues that created barriers to the center's success, and the center was ultimately closed.